Student Activities Proposal Evaluation System Planning Using Barcode Scanner Technology - Rizqi Chandra Pramana (International Journal of Computer, Network Security and Information System, 2020)
Student Creativity Program (PKM) is an activity formed by Ministry of Research and Technology of the Republic of Indonesia. This activity was formed to facilitate the various potentials possessed by students to apply and develop the knowledge gained in lectures to the wider community. PKM Center is the agency that manages student creativity program proposals in Universitas Pembangunan Nasional “Veteran” Jawa Timur enviroment. However, the management of student proposal data carried out by the PKM Center is still done manually. So it is difficult to evaluate the history of student proposals. Because of these problems, information systems need to be developed to ensure that these problems can be resolved. So that the management of student proposal data can be carried out properly. Making a student proposal evaluation system has several stages that are carried out, such as a literature study to get a reference to the features used in the proposal evaluation system. After that, it is continued with business process design to application design. Barcode scanners as supporting technology are used in the system to improve data accuracy. The final result of this research is a web-based system for evaluating proposals that have been submitted by the proposing students, so that the proposal data can be used by the center in determining which proposals can qualify for the next stage.